ANALYSIS OF RECEIVABLES FOR PROFITABILITY AT SAHID JAYA HOTEL INTERNATIONAL, TBK IN THE INDONESIA STOCK EXCHANGE - Hanafie, Hadriana (Universitas Patria Artha, 2018)
ABSTRACTThe research objectives are: 1) To find out and analyze the receivable turnover rate andprofitability value at Sahid Jaya International Hotel, Tbk on the Indonesia Stock Exchange.Data sources are secondary data which is data obtained from Sahid Jaya International, Tbk Hotel documents on the Indonesia Stock Exchange in the form of financial financial statementsin the form of financial position reports and comprehensive income reports.The results of the research show that 1) the accounts receivable turnover of Sahid JayaInternational, Tbk hotels in the Indonesia Stock Exchange is in good condition. The results ofthe analysis on the activity ratio include increasing receivable turnover, 2) The averagecollection age of accounts receivable showing the accounts of Sahid Jaya International, Tbk inthe Indonesia Stock Exchange in 2016 to 2017 is in a good condition because it has decreasedevery year and accelerate receivables into company cash, and 3) The results of the analysis onprofitability ratios show that the profitability conditions of Sahid Jaya International, Tbk Hotelsin the Indonesia Stock Exchange in 2016 to 2017 have increased every year, this means thecompany has succeeded in obtaining profit.